Interplay Between Risk Perception, Behavior, and COVID-19 Spread - Dönges, Philipp; Wagner, Joel; Contreras, Sebastian; Iftekhar, Emil N.; Bauer, Simon; Mohr, Sebastian B.; Dehning, Jonas; Calero Valdez, André; Kretzschmar, Mirjam; Mäs, Michael; Nagel, Kai; Priesemann, Viola (Frontiers in Physics, 2022)
Pharmaceutical and non-pharmaceutical interventions (NPIs) have been crucial for controlling COVID-19. They are complemented by voluntary health-protective behaviour, building a complex interplay between risk perception, behaviour, and disease spread. We studied how voluntary health-protective behaviour and vaccination willingness impact the long-term dynamics. We analysed how different levels of mandatory NPIs determine how individuals use their leeway for voluntary actions. If mandatory NPIs are too weak, COVID-19 incidence will surge, implying high morbidity and mortality before individuals react; if they are too strong, one expects a rebound wave once restrictions are lifted, challenging the transition to endemicity. Conversely, moderate mandatory NPIs give individuals time and room to adapt their level of caution, mitigating disease spread effectively. When complemented with high vaccination rates, this also offers a robust way to limit the impacts of the Omicron variant of concern. Altogether, our work highlights the importance of appropriate mandatory NPIs to maximise the impact of individual voluntary actions in pandemic control.